The Effect Of Compliance Calcium Supplementation modification Tablet On Calcium and Blood Pressure In Pregnant Women - Dahniarti, Dhany; Idris, Irfan; Am, Nasrudin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Palapa Nusantara Lombok NTB, 2018)
A low intake of calcium leads to an increase in high blood pressure by stimulating the release of paratiroid and  renin hormones that lead to increase in intracellular calcium concentration in the vasculer smooth muscle cells and result in vasocontriction. This study aims to determine the influence of compliance to supply modified calcium tablet toward calcium level and blood pressure in pregnant mothers. This research was conducted at RSIA Sitti Khadijah I Maternity Hospital Makassar with research design of quasy experiment with pre-post test group control design. There were 30 pregnant mother sampels of prehypertension in gestational age> 20 weeks, 12 pregnant women were given normal calcium tablets and 18 pregnant women given modified calcium tablets for 8 weeks each. Data analysis use paired t test. The results indicate that there is a different changes of calcium level and blood pressure between pregnant mothers of intervention group and control group with the value of p = 0.000 (p<0.05). After intervention averagely the calcium level increase in intervention group 0.4 mg/dl while in control group 0.1 mg/dl, followed by the average decrease in blood pressure of systole and dyastole in the intervention group 15.4/9.6 mmHg while in the control group 3.5/4.5 mmHg.